Generating of A Dynamic and Secure S-Box for AES Block Cipher System Based on Modified Hexadecimal Playfair Cipher - Newroz Nooralddin Abdulrazaq (Zanco Journal of Pure and Applied Sciences, 2024)
In today's digital world, the extensive use of devices, including smartphones, tablets, IoT devices, and the internet, emphasizes the necessity for strong security measures. These measures are essential to safeguard both user data and sensitive government information. As technology advances, the enhancement of cryptographic methods becomes imperative, ensuring alignment with this rapid progression. This paper introduces a novel approach to encrypting classified data using the modified AES cipher system. It employs a dynamic and secure substitution byte operation with a 4×4 matrix, replacing the static and public 16×16 S-box found in the original version of AES. To construct the presented S-box, the system makes a secret key of 56 bytes (4×14 Rounds), where each round of the AES-256 utilizes 4 bytes to generate a 4×4 Hexadecimal Playfair matrix. By altering the S-boxes in each round and block (where each block utilizes AES key expansion to generate a 56-byte secret key for the Playfair matrix), it becomes feasible to produce distinct encrypted blocks even when the original blocks remain identical. In terms of security, the effectiveness of the provided method has been verified by experimental and analytical studies including the Avalanche effect, Balanced output, Hamming distance, and Time complexity. The result shows that the Avalanche effect of the proposed method exceeds 50% and increase the time of brute force attack. Moreover, the proposed algorithm exhibits impressive execution speed, handling approximately 200 KB in just one second.